ELASTICITY OF BITUMEN BINDERS AND THE FACTORS CAUSING IT - Galkin, A.; Галкін, А. В.; Галкин, А. В. (Харьковский национальный автомобильно-дорожный университет, 2015)
The article deals with the influence of the initial bitumen penetration grade and different concentrations of the mineral filler on the elasticity of the polymer-modified bitumen (PMB) with 3 and 6 % of SBS type polymer. The dependences of elasticity of the PMB on the test conditions – such as the temperature and the stress state level are shown additionally.
ЕЛАСТИЧНІСТЬ БІТУМНИХ В’ЯЖУЧИХ, ТА ФАКТОРИ ЩО ЇЇ ОБУМОВЛЮЮТЬ
ЭЛАСТИЧНОСТЬ БИТУМНЫХ ВЯЖУЩИХ, И ФАКТОРЫ ЕЁ ОБУСЛАВЛИВАЮЩИЕ
Keywords: elasticity; polymer-modified bitumen; ductility; mineral filler; penetration grade; еластичність; модифікований полімером бітум; дуктильність; мінеральний порошок; марка бітуму; эластичность; модифицированный полимером битум; дуктильность; минеральный порошок; марка битума; 665.775:678.01:539.389